Usefulness of the Brief Scale for Psychiatric Problems in Orthopaedic Patients (BS-POP) for Predicting Poor Outcomes in Patients Undergoing Lumbar Decompression Surgery. (21st December 2021) - Watanabe, Kazuyuki; Otani, Koji; Nikaido, Takuya; Kato, Kinshi; Kobayashi, Hiroshi; Handa, Junichi; Yabuki, Shoji; Kikuchi, Shin-Ichi; Konno, Shin-Ichi
Abstract : Background . The Brief Scale for Psychiatric Problems in Orthopaedic Patients (BS-POP) is an original questionnaire that evaluates psychosocial problems in orthopaedic patients. The purpose of this study was to clarify the relationship between BS-POP scores and surgical outcomes in patients with lumbar spinal stenosis (LSS). Methods . From our database, a total of 157 patients with LSS who had undergone decompression surgery and completed a 1-year follow-up were retrospectively observed. The primary outcome was the numerical rating scale (NRS) score for satisfaction with surgery (from 0: not satisfied to 10: completely satisfied). Patients with an NRS score ≥8 were classified into the satisfied group. The secondary outcomes were NRS scores for low back pain, leg pain, and leg numbness and scores on the Roland–Morris Disability Questionnaire (RDQ). BS-POP was used to detect psychiatric problems before surgery. A BS-POP score ≥11 on the physician version or a combination of 10 on the physician version and ≥15 on the patient version was considered to indicate the presence of psychiatric problems. The patients were classified into two groups and compared based on preoperative BS-POP scores at the 1-year follow-up. Results . Preoperatively, 22 and 135 patients showed high and low BS-POP scores, respectively. No significant differences in preoperative symptoms were found between the two groups. At 1 year after surgery, patients with high BS-POP scores showed significantly lower satisfaction with surgery, higher NRS scores for low back pain, leg pain, and leg numbness, and lower RDQ deviation scores than did the low BS-POP group (p < 0.05 ). The results of the multivariable analysis indicated that preoperative high BS-POP scores were independently associated with low satisfaction with surgery (odds ratio: 5.2, 95% confidence interval: 1.9–15.1). Conclusion . High preoperative BS-POP scores were associated with poor outcomes for decompression surgery in patients with LSS at 1 year after surgery. These results suggest that BS-POP is a useful tool for predicting surgical outcomes in patients with LSS.